Current Strategies in Developing Antibacterial Surfaces for Joint Arthroplasty Implant Applications - Cardoso, Giovana Collombaro [UNESP]; Correa, Diego Rafael Nespeque [UNESP]; Fosca, Marco; Pometun, Evgenii V.; Antoniac, Iulian V.; Grandini, Carlos Roberto [UNESP]; Rau, Julietta V. (MDPI, 2025)
Prosthetic joint infections (PJIs) remain a significant challenge, occurring in 1% to 2% of joint arthroplasties and potentially leading to a 20% to 30% mortality rate within 5 years. The primary pathogens responsible for PJIs include Staphylococcus aureus, coagulase-negative staphylococci, and Gram-negative bacteria, typically treated with intravenous antibiotic drugs. However, this conventional approach fails to effectively eradicate biofilms or the microbial burden in affected tissues. As a result, innovative strategies are being explored to enhance the efficacy of infection prevention through the development of antibacterial-coated implants. These coatings are required to demonstrate broad-spectrum antimicrobial activity, minimal local and systemic toxicity, favorable cost-effectiveness, and support for bone healing. In the present review, the analysis of various methodologies for developing antibacterial coatings was performed, emphasizing studies that conducted in vivo tests to advance potential clinical applications. A diversity of techniques employed for the development of coatings incorporating antimicrobial agents highlights promising avenues for reducing infection-related surgical failures.
Keywords: antibacterial coatings; antibacterial surfaces; antimicrobial coatings; biomedical implants; implants; surface treatments